2016
DOI: 10.1016/j.ebiom.2016.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Entorhinal Principal Neurons Mediate Brain-stimulation Treatments for Epilepsy

Abstract: Brain stimulation is an alternative treatment for epilepsy. However, the neuronal circuits underlying its mechanisms remain obscure. We found that optogenetic activation (1 Hz) of entorhinal calcium/calmodulin-dependent protein kinase II α (CaMKIIα)-positive neurons, but not GABAergic neurons, retarded hippocampal epileptogenesis and reduced hippocampal seizure severity, similar to that of entorhinal low-frequency electrical stimulation (LFES). Optogenetic inhibition of entorhinal CaMKIIα-positive neurons bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 52 publications
(60 reference statements)
0
23
1
1
Order By: Relevance
“…The fewer number of GAD neurons compared with eYFP-labeled neurons was likely due to the detection limitation of GAD antibody. We designed opto-electrodes that allow optogenetic stimulation during in vivo single-unit recordings in the SNr of urethaneanesthetized mice 32 . Representative peri-event histograms confirmed that blue-light stimulation (473 nm, 20 Hz, 10 ms, 5 mW, 10 s on-off cycle) excited 15 out of 19 SNr GABAergic neurons from 3 Vgat-ChR2-eYFP mice, suggesting that SNr GABAergic neurons can be functionally activated by blue-light stimulation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fewer number of GAD neurons compared with eYFP-labeled neurons was likely due to the detection limitation of GAD antibody. We designed opto-electrodes that allow optogenetic stimulation during in vivo single-unit recordings in the SNr of urethaneanesthetized mice 32 . Representative peri-event histograms confirmed that blue-light stimulation (473 nm, 20 Hz, 10 ms, 5 mW, 10 s on-off cycle) excited 15 out of 19 SNr GABAergic neurons from 3 Vgat-ChR2-eYFP mice, suggesting that SNr GABAergic neurons can be functionally activated by blue-light stimulation.…”
Section: Resultsmentioning
confidence: 99%
“…The SNr-PF circuit may act like an intrinsic feed-forward amplifier; it may respond to abnormal cortical information input through basal ganglia circuit during seizures (as demonstrated by our fiber photometry showing the increased SNr PV neural dynamics), and thus in turn regulate epileptic networks via thalamocorticalhippocampal circuits. Specifically, connections between the PF and the entorhinal cortex 55 , the major source of cortical projections to the hippocampus 32,58 , are likely involved in these modulatory effects. Although abnormalities in the PF still need to be clarified for a better understanding of the abnormal network in seizure propagation, here we identified inhibition of PF GABAergic neurons by SNr PV projections as an important mechanism allowing for precise regulation of TLE.…”
Section: Discussionmentioning
confidence: 99%
“…To verify whether the virus was functional in vivo, neuronal spikes were recorded and analyzed in PV-hM3Dq and CaMKII2α-hM4Di mice which were anesthetized by urethane as our previous studies. 28 To test the neuronal response in hippocampal seizure, single-unit recordings were performed and analyzed in urethane-anesthetized wildtype mice. Putative pyramidal neurons and GABAergic neurons were distinguished by three independent criteria (firing rate, spike width, and autocorrelation pattern) based on previous studies.…”
Section: In Vivo Single-unit Recordings and Analysismentioning
confidence: 99%
“…For instance, a pre-ictal spiking regime mediated by GABA B interneurons may be aborted by using lower stimulation frequencies than a pre-ictal spiking regime mediated by GABA A interneurons, since GABA B interneurons have slower kinetics than GABA A interneurons. Depending on the neuroanatomy and neurophysiology of a specific brain region (type of subpopulations and connections between them), activation of specific types of interneurons can be achieved via the modulation of different neural targets [57,58,60,[76][77][78].…”
Section: Discussionmentioning
confidence: 99%